2017
DOI: 10.3233/ch-15081
|View full text |Cite
|
Sign up to set email alerts
|

Rheological alteration of erythrocytes exposed to carbon nanotubes

Abstract: Single-walled carbon nanotubes (SWNTs) have been increasingly used in a variety of biomedical applications, such as in vivo delivery of drugs and tumor imaging. Potential exposure of SWNTs to human red blood cells (RBCs) may cause serious toxicity including alteration of mechanical properties of cells. The present study investigated the cellular response to exposure of SWNTs with measuring rheological characteristics of RBCs, including hemolysis, deformability, aggregation, and morphological changes. RBCs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…CNT dispersion seems to be a factor influencing their hemocompatibility, as proven by a recent study showing that bundled SWCNTs had higher hemolytic activity respect to dispersed SWCNTs and induced significant modifications of RBC shape and fusion [175].…”
Section: Carbon Nanotubesmentioning
confidence: 97%
See 1 more Smart Citation
“…CNT dispersion seems to be a factor influencing their hemocompatibility, as proven by a recent study showing that bundled SWCNTs had higher hemolytic activity respect to dispersed SWCNTs and induced significant modifications of RBC shape and fusion [175].…”
Section: Carbon Nanotubesmentioning
confidence: 97%
“…Aggregation and activation [160] -Activation through classical pathway (C1q binding) [145] No internalization, no toxicity [172]. Shape modification, fusion and hemolysis from bundled SWCNTs [175] Accelerated thrombus formation in the microcirculation [162,163]. Amplification of vascular thrombosis in rats (carotid artery) [160] -COOH Activation and formation of platelet-granulocyte complexes [167] Activation of the contact pathway [159] -Dose-and time-dependent hemolysis [173] Toxic effect on erythrocytes and transient anemia in mice [173] MW CNTs Pristine Aggregation, activation [160,165] and formation of PMPs [164].…”
Section: Sw Cnts Pristinementioning
confidence: 99%
“…9 Single-walled carbon nanotubes (SWNTs) were demonstrated to enter into erythrocytes by the way of "membrane encapsulation" or "endocytosis", and experimental results showed that bundled SWNTs could cause cell-cell fusion and had higher hemolytic activity than individual SWNTs alone. 10 In addition to the toxic effects on erythrocytes, NPs have also been found to be able to protect erythrocytes somehow. Jacek Grebowski et al irradiated human erythrocytes with 6 MeV high-energy electrons with 150 mg mL À1 of polyhydroxylated fullerene C 60 (fullerenol C 60 (OH) 36 ), and found that the presence of fullerenol C 60 (OH) 36 protected erythrocytes from hemolysis induced by high-energy electron irradiation, and the protective effect became much stronger with irradiation intensity and irradiation time.…”
Section: Spherocytes and Echinocytesmentioning
confidence: 99%
“…The detection of hematological rheology indicators such as erythrocyte deformation index, rigidity index, and aggregation index can help us gain keen insights into the interactions between nanoparticles and erythrocytes to evaluate the severity of nanoparticle cytotoxicity. [76][77][78] Ran et al found that Fe 3 O 4 - MNPs signicantly affected indicators of mechanical properties of erythrocytes, such as erythrocyte deformation index, rigidity index, aggregation index, and erythrocyte electrophoresis time, but little is known about the mechanism. 63 The shape, size, concentration, surface modication, and incubation time of the nanoparticles signicantly affected the deformation index and aggregation index of erythrocytes under the same shear stress conditions.…”
Section: Hemorheologymentioning
confidence: 99%
See 1 more Smart Citation